Penerapan Preseden Desain Frank Lloyd Wright Pada Panti Jompo Di Kota Pekanbaru - Faudya Agiasty; Yohannes Firzal; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The advancement of the health sector has an impact on life expectancy which is getting higher and along with the increase of the elderly population. The City of Pekanbaru has the highest projection of the number of elderly people in Riau Province. This is a problem because in Pekanbaru only has a nursing home that is out of balance with an increase in the number of elderly people so that a nursing home is needed that provides an alternative place of residence for the elderly. Nursing homes with Frank Lloyd Wright's organic architectural design precedents provide a decent atmosphere for the residents, not just a home for the elderly but by making art created by the aesthetics of building design. Frank Lloyd Wright's design precedents were used as an effort to realize the design of nursing homes that could stimulate the elderly by bringing them closer to nature. Therefore, a nursing home is needed in the city of Pekanbaru with the design precedent of Frank Lloyd Wright. Keywords: Nature, Organic Architecture, Frank Lloyd Wright, Nursing Home